Stack Development and Industrial Scale-Up. (10th July 2019) - Geipel, Christian; Hauptmeier, Karl; Herbrig, Kai; Mittmann, Frank; Münch, Markus; Pötschke, Martin; Reichel, Ludwig; Strohbach, Thomas; Seidel, Tobias; Surrey, Alexander; Walter, Christian
Abstract : Sunfire commercially distributes products for various markets (SOFC, SOEC and Co-SOEC) with its stack and system technology. To achieve an ideal tradeoff between cost, performance, and degradation for its customers, Sunfire's stack design is continuously being improved. In this publication, latest results that resulted in a decrease of the combined life cycle costs (€ kW -1 h -1 ) of approx. 40% and cost projections for large scale production will be presented. Furthermore, recent changes in automation and industrial scale-up that lead to a current annual production volume of >10MW and next steps to further increase this value will be shown. Last but not least, updates on the recent development for Sunfire's products Home, Remote and Hylink/Synlink will be given.